Princípios de uma usina fotovoltaica: uma aplicação ao ensino médio - Astrath, Eduardo Augusto Castelli (2015)
This paper describes the way was developed and applied an educational product for teaching Physics, with the third year of high school. It is a prototype of electricity generation via solar panel. The main motivation was the fact that it is common for issues of electricity and magnetism be addressed more in mathematical form (problem solving) than physical that involves, besides not being given all the content provided by the curriculum menu. In addition, the fact that the curriculum component Modern Physics is poorly explored due to the number of hours available in the classroom. There was also the concern to bring students a greater insight into a much discussed topic today, which is the generation of electricity, through processes considered clean, ie that do not damage the environment. This application allowed us to report the influence of a theoretical and experimental activity in significant student learning. As a theoretical foundation for better analysis we used the concept of meaningful learning and concept maps studied respectively by Ausubel and Novak. Thus, the analysis of material was through a questionnaire with specific knowledge relating to the product, the curricular component and related to the daily lives of students. And a concept map on the topic electricity and magnetism. This product and the way the evaluation was applied in a class of 19 students of a public school in the city of Maringa-PR. The results were satisfactory, it can be assessed that the majority of students reached the proposed goal, understanding the physics that is behind the mathematical equations in the proposed content and phenomena related to modern physic.